Fathers’ imprisonment as perceived by their children - Domżalska, Aneta (Forum Pedagogiczne, 2022)
The author presents the results of a study on selected aspects of fathers’ imprisonment from the perspective of their children. The study included 72 children, aged 12 to 18 years, whose fathers were imprisoned in penal institutions in Poland. The analysis of results revealed that all of the children knew that their fathers were serving a prison sentence. Most children report unpleasant emotions related to this fact, such as regret, sadness, anger, and shame. On the other hand, the vast majority of the children understood that their parent had made a mistake and that they were bearing the consequences of their act. The vast majority of respondents maintained contact with their fathers (e.g., visitations, telephone calls, letters), but the frequency of these contacts was quite low. The children claimed that during contact with their fathers they experienced various emotions: from nervousness, sadness, and shame at where their parent was, to satisfaction with and joy at the possibility of meeting the father. The vast majority of prisoners’ children reported that the frequency and quality of their contact with the father was inadequate and suggested changes. Taking account of prisoners’ children’s perspective, the study encourages further local research addressing this issue.